BEHAVIORAL FACTORS OF MICRO, SMALL AND MEDIUM ENTERPRISES ON DECISIONS IN CHOOSING ISLAMIC BANKING PRODUCTS IN RIAU PROVINCE - Saputra, Hendra Eka (Jurnal Syarikah : Jurnal Ekonomi Islam, 2025)
Micro, Small and Medium Enterprises (MSMEs) are increasingly aware of the role of Islamic banks in creating and maintaining competitive advantages in the economy, especially affecting MSMEs. The trend in choosing Islamic banks is an attraction from the phenomenon that is currently occurring among micro, small and medium enterprises in encouraging the sustainability of the business they are engaged in. Therefore, this paper examines the extent to which factors influence MSMEs in deciding to use products at Islamic banks. This type of research is quantitative. with secondary data processing. Primary and secondary data sources. With respondents being MSMEs through Google Form. This study analyzes the relationship between organizational culture, socialization, individual productivity, and employee satisfaction and achievement using the Structural Equation Modeling - Partial Least Squares (SEM-PLS) method. The results of the analysis show that organizational culture has a significant effect on employee satisfaction (t = 30.22, p < 0.05), while socialization does not directly affect employee satisfaction (t = 0.52, p > 0.05). However, socialization has a positive impact on individual productivity (t = 6.59, p < 0.05), which ultimately improves employee performance (t = 16.47, p < 0.05). This finding confirms the importance of organizational culture in improving job satisfaction as well as the role of individual productivity in achieving work performance. Therefore, organizations need to optimize socialization strategies that not only improve productivity but also contribute to job satisfaction.